2007
DOI: 10.1371/journal.pgen.0030078
|View full text |Cite
|
Sign up to set email alerts
|

p53 Activation by Knockdown Technologies

Abstract: Morpholino phosphorodiamidate antisense oligonucleotides (MOs) and short interfering RNAs (siRNAs) are commonly used platforms to study gene function by sequence-specific knockdown. Both technologies, however, can elicit undesirable off-target effects. We have used several model genes to study these effects in detail in the zebrafish, Danio rerio. Using the zebrafish embryo as a template, correct and mistargeting effects are readily discernible through direct comparison of MO-injected animals with well-studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
850
2
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 939 publications
(876 citation statements)
references
References 35 publications
(55 reference statements)
21
850
2
3
Order By: Relevance
“…Fig. S1C,D; Robu et al, 2007), suggesting that the gene expression changes are directly caused by the mutation.…”
Section: Resultsmentioning
confidence: 96%
“…Fig. S1C,D; Robu et al, 2007), suggesting that the gene expression changes are directly caused by the mutation.…”
Section: Resultsmentioning
confidence: 96%
“…Acridine orange staining showed similar patterns of apoptosis (data not shown). It is known that offtarget effects of MOs could be mediated through tumor suppressor p53-induced apoptosis (Robu et al, 2007). As the p53 protein was shown to be up-regulated in the microarray analysis of gr ATG1 MO embryos at 5 and 10 hpf (see below), we examined the occurrence of possible off-target effects by co-injecting an anti-p53 MO with gr ATG1 MO or gr ATG2 MO.…”
Section: Inhibition Of Gr Mrna Translation Results In Increased Embrymentioning
confidence: 99%
“…An antisense splice variant MO was designed on the sequence at the exon 3-intron 3-junction, MO4-nr3c1 (gr splic MO): 5 0 -GCC AGA GAT ATA TGG AAT ACC TTC A-3 0 (the exon complementary sequence is underlined). Finally, we used an MO against the ATG translation initiation site of p53 mRNA (MOp53): 5 0 -GCG CCA TTG CTT TGC AAG AAT TG-3 0 (named MO4-tp53 by Robu et al, 2007).…”
Section: Morpholinosmentioning
confidence: 99%
“…It has been shown that non-specific cell death caused by morpholinos can be due to an upregulation of p53, which modulates a variety of pro-apoptotic genes (Miyashita et al, 1994;Roperch et al, 1998;Robu et al, 2007). To test whether the cell death in r2, r3, and r5 is specific to gbx2 knockdown, we co-injected embryos with p53-MO to minimize non-specific apoptosis.…”
Section: Gbx2 Knockdown Decreases Cell Proliferation and Increases Cementioning
confidence: 99%
“…A dose of 8 ng was used. For p53 morpholino, we used a concentration of 3 ng/nl as previously described (Robu et al, 2007). We estimated the dose per embryo based upon the concentration of the MO solution, and the diameter (volume) of the injection bolus in the yolk cell.…”
Section: Morpholino and Rna Injectionsmentioning
confidence: 99%